Acehnese Language Shift and Its Impact to Young Generation - Ismail, Fitriah; Fhonna, Rahmi; Nasir, Khairun (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2021)
Language shift means replacing one language to another as a communication tool within a community. This study intends to investigate the factors that cause language shift among Acehnese and its impact to the young generations of Acehnese language users. The study reveals that there are two factors causing a shift in Acehnese language, namely: the external factors (i.e., culture, economy, and inter-generational transfer) and (2) internal factors (i.e, language attitude and language ability). In addition to the impact of language use, the study points out that although most of the Acehnese people are able to speak their own community language, their children are rapidly losing their language.